ASPEK HUKUM PEMANFAATAN TEKNOLOGI INFORMASI DALAM PERSPEKTIF UU NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Go Lisanawati; Mufidatul Ma'sumah (Widya Yuridika, 2019)
The use of information technology (IT) at present plays an important role and at last may beara new society namely the users of IT as a part of information and communication technologysociety. On the one hand, the development may provide the users with unlimited information.On the other hand, the IT may also be misused for crimes. In this condition, law should be ableto serv some protection for their users.